KUALITAS AUDIT, CORPORATE SOCIAL RESPONSIBILITY, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Kartika Khairunisa; Dini Wahjoe Hapsari; Wiwin Aminah (JRAK, 2017)
This research aims to analyze and test the influence of audit quality, corporate social responsibility, and company size compensation against tax avoidance on food and beverage manufacture companies listed in Indonesia Stock Exchange (BEI) in 2011-2015. The population in this research is a food and beverage manufacture company listed in Indonesia Stock Exchange (BEI) in 2011-2015. The sampling techniques used are namely puposive sampling and 10 food and beverage manufacture companies with the period of observation for 5 (five) years so we can get 50 units of samples in this research. Data analysis methods in this research is a panel data regression analysis. The results of the study showed that the audit quality, corporate social responsibility, and company size compensation simultaneously affect a significant tax avoidance. Partially, audit quality and corporate social responsibility negatively effect significant tax avoidance, while company size compensation does not affect a significant tax avoidance.